2013
DOI: 10.1111/bcp.12098
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of rituximab with or without plasmapheresis in kidney patients with antibody‐mediated disease

Abstract: Aims Both rituximab and plasmapheresis can be associated in the treatment of immune‐mediated kidney diseases. The real impact of plasmapheresis on rituximab pharmacokinetics is unknown. The aim of this study was to compare rituximab pharmacokinetics between patients requiring plasmapheresis and others without plasmapheresis. Methods The study included 20 patients receiving one or several infusions of rituximab. In 10 patients, plasmapheresis sessions were also performed (between two and six sessions per patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 29 publications
(33 reference statements)
0
42
0
1
Order By: Relevance
“…Several studies have shown a remarkable increase in RIT clearance in thrombotic thrombocytopenic purpura or kidney transplant recipients by TPE performed within 1-3 days of RIT infusion (28,29); however, these studies did not analyze the impact of TPE on the therapeutic efficacy of RIT. Darabi et al (30) suggested that regularly scheduled TPE did not diminish the immunosuppressive effects of RIT due to the rapid effects of RIT on circulating CD20þ in a study with two thrombocytopenic purpura patients who were given RIT 24-36 hours before TPE.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown a remarkable increase in RIT clearance in thrombotic thrombocytopenic purpura or kidney transplant recipients by TPE performed within 1-3 days of RIT infusion (28,29); however, these studies did not analyze the impact of TPE on the therapeutic efficacy of RIT. Darabi et al (30) suggested that regularly scheduled TPE did not diminish the immunosuppressive effects of RIT due to the rapid effects of RIT on circulating CD20þ in a study with two thrombocytopenic purpura patients who were given RIT 24-36 hours before TPE.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacokinetics of rituximab were described in 12 pharmacokinetic modelling studies in NHL, CLL and rheumatoid arthritis . and in patients under plasmapherisis . Some of these studies suggested that rituximab pharmacokinetics might be influenced by antigen mass (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, rituximab was shown to hasten platelet count recovery, reduce plasma Additional Supporting Information may be found in the online version of this article. 1 Service de M edecine Interne, CHU Charles Nicolle, Rouen; 2 Inserm U1096, Rouen, France; 3 Hôpital Saint-Antoine, AP-HP, Centre de R ef erence des Microangiopathies Thrombotiques, Paris, France; 4 Universit e François-Rabelais de Tours, CNRS, GICC UMR 7292, CHRU de Tours, Laboratoire de Pharmacologie-Toxicologie, Tours, France; 5 Hôpital Saint-Louis, AP-HP, Service de R eanimation M edicale, Paris, France; 6 Universit e Paris Diderot, Sorbonne Paris Cit e, Paris, France; 7 Hôpital de Marseille Conception, Service d'H emaph erèse, Marseille, France; 8 Hôpital Saint-Louis, AP-HP, Service d'Immunologie Clinique, Paris, France; 9 CHU Saint-Antoine, AP-HP, Service de R eanimation M edicale, Paris, France; 10 Sorbonne Universit e, UPMC Univ Paris 06, Paris, France; 11 Urgences n ephrologiques et transplantation r enale, Hôpital Tenon, AP-HP, Paris, France; 12 Hôpital Cochin, AP-HP, Service de R eanimation Polyvalente, Paris, France; 13 Universit e Paris 5, Paris, France; 14 Hôpital Sud, Service de N ephrologie-M edecine Interne, Amiens, France; 15 Service de M edecine interne 1, Hôpital La Piti e-Salpêtrière, AP-HP, Paris, France; 16 Service de M edecine interne, CHU de Fort-de France, France; 17 Hôpital Saint-Antoine, AP-HP, Unit e de Recherche Clinique de l'Est Parisien (URC-Est), Paris, France; 18 CHU Saint-Antoine, AP-HP, Service d'Immunologie et H ematologie biologique, Paris, France; 19 Hôpital Lariboisière, AP-HP, Service d'H ematologie Biologique, Paris, France; requirement and decrease the 1-year relapse rate by diminishing the production of anti-ADAMTS13 and restoring ADAMTS13 activity [9,10,12]. Additionally, preemptive rituximab infusions administered to patients with a persistent severe ADAMTS13 deficiency during TTP remission efficiently prevent long-term relapses [13].…”
Section: Introductionmentioning
confidence: 99%